FACTORS ASSOCIATED WITH SUBJECTIVE COMPLAINTS OF EYE FATIGUE IN TAILOR WORKERS AT THE CHILDREN'S PALACE MARKET, JAMBI CITY - Dwi Rohmawati; Putri Sahara Harahap; Parman Parman (Sekolah Tinggi Pariwisata Mataram, 2023)
Sewing is one of the jobs that requires accuracy and sharpness of the eyes so that it will be at risk for experiencing eye fatigue. Risk factors for eye fatigue are lighting intensity, age, years of service and history of eye disease. The Children's Palace Market is the central tailor in Jambi City. The purpose of this study was to determine the factors associated with eye fatigue in tailors at the Children's Palace Market. The study used a cross sectional design. The research sample was 30 tailors at the Istana Children's Market in Jambi City. The sampling technique used was the total population technique. The research instrument was a questionnaire and a lux meter. Data were analyzed by univariate and bivariate using independent t test and Mann Whitney test. As many as 60.0% of respondents experienced subjective complaints of eye fatigue, the average lighting in the respondent's work room was 227.96 lux, the average working period of the respondents was 17.40 years with a standard deviation of 8.654 years and the average length of service of the respondents was 7.87 hours/day. The results of the bivariate analysis showed that there was a relationship between lighting (p = 0.001), working period (p = 0.000) and length of work (p = 0.000) with subjective complaints of eye fatigue on tailors at the Children's Palace Market.